e-Tourism, Personal Technology Post-Adoption Behavior, and Sustainable Behavior Intention in Indonesia - Merinda Pandowo; Imelda W. J. Ogi; Claudia Wanda Melati Korompis; Christoffel Mardy Oktarisa Mintardjo (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
E-tourism's behavior of e-tourism in minimizing the use of natural resources and costs gives birth to sustainable behavior in the form of environmentally friendly tourism and digital technology. This study aims to examine the effects of technology-based post-adoption behavior by tourists that lead to sustainable behavior. Predictors of technology usage using some of the UTAUT2 models. The survey was conducted in Indonesia on respondents in Manado who obtained as many as 100 participants, which were then analyzed using path analysis. The research findings show that the UTAUT 2 model, namely the relationship between hedonic motivation, price value, and habit, affects sustainable behavior mediated by behavior intention. These findings contribute to the development of technology-based marketing and tourism management. Some limitations, as well as implications, are also disclosed in this article.